Resin composition and rotor
Patent Information
- Application Number
- JP2025061655
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
【0006】 本発明によれば、誘導電機に用いられる回転子の放熱特性を向上させることができる。
Smart Images

Figure 2026168533000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a resin composition and a rotor.
BACKGROUND ART
[0002] As a technique using a resin material for a rotor, there is one described in Patent Document 1 (Japanese Unexamined Patent Application Publication No. 6877657). This document discloses a technique of forming an insulating layer in a slot of a rotor of an induction motor by applying an insulating paint containing silicone resin to the inner peripheral surface of the slot that accommodates a conductor.
PRIOR ART DOCUMENTS
PATENT DOCUMENTS
[0003]
PATENT DOCUMENT 1
SUMMARY OF THE INVENTION
PROBLEMS TO BE SOLVED BY THE INVENTION
[0004] In an induction motor, an alternating current is passed through a stator to generate an induced current in a rotor, and the rotor rotates due to the interaction between the current and a rotating magnetic field. At this time, heat is generated in the rotor. In recent years, along with the higher output of induction motors, requirements for heat dissipation have become greater than ever before. The present invention has been made in view of the above problems, and an object thereof is to provide a technique for improving the heat dissipation characteristics of a rotor used in an induction electric machine.
MEANS FOR SOLVING THE PROBLEMS
[0005] According to the present invention, the following techniques are provided. 1. A resin composition for use in a rotor having a laminated iron core formed by laminating a plurality of electromagnetic steel sheets, and a conductor (metal rod) extending in the lamination direction of the laminated iron core, the resin composition being: The resin composition contains a thermosetting resin (excluding silicone resin). 2. The resin composition according to 1, wherein the thermosetting resin comprises one or more materials selected from the group consisting of epoxy resin, phenolic resin, nylon, and urethane. 3. The resin composition according to 1. or 2., wherein the glass transition temperature of the thermosetting resin is 145°C or higher. 4. The resin composition according to any one of 1 to 3, wherein the filler content in the thermosetting resin is 70% by mass or more and 95% by mass or less, based on the total mass of the thermosetting resin. 5. The resin composition according to any one of 1 to 4, wherein the average particle size D50 in the particle size distribution of the filler contained in the thermosetting resin is 1 μm or more and 10 μm or less. 6. The resin composition according to any one of 1 to 5, wherein the thermosetting resin is solid. 7. The resin composition according to any one of 1 to 6, wherein the thermal conductivity of the thermosetting resin is 0.5 W / m·K or higher. 8. The resin composition according to any one of 1 to 7, wherein the thermosetting resin contains a thermal conductive filler. 9. The conductor is positioned outside the side surface of the laminated iron core, The resin composition is used to fill at least a portion of the space between the conductor and the laminated iron core, as described in any one of 1 to 8. 10. The rotor has through holes provided in the stacking direction of the stacked iron core, The conductor extends inside the through hole, The resin composition is used to fill at least a portion of the gap between the through hole and the conductor, as described in any one of 1 to 9. 11. The rotor has through holes provided in the stacking direction of the stacked iron core, and a short-circuit portion (short-circuit ring) that short-circuits a plurality of conductors protruding from the through holes, The resin composition is used to fill at least a portion of the space between the short-circuit portion and the laminated iron core, as described in any one of 1 to 10. 12. A laminated iron core made by stacking multiple steel plates, Multiple conductors (metal rods) are arranged on the side surface of the laminated iron core, A first member provided in at least a portion between the conductor and the laminated iron core, It has, The rotor is formed of the resin composition described in any one of 1 to 11., wherein the first member is a rotor. 13. A laminated iron core made by stacking multiple steel plates, The through holes provided in the stacking direction of the laminated iron core, A conductor (metal rod) is placed in the through hole, A second member formed in the gap between the through hole and the conductor, It has, A rotor, wherein the second member is formed of the resin composition described in any one of 1 to 11. 14. A laminated iron core made by stacking multiple steel plates, The laminated core has a through hole that penetrates from one end to the other in the lamination direction, A conductor (metal rod) is placed in the through hole, A short-circuit ring formed by short-circuiting multiple conductors protruding from the through-hole, A third member formed in the space between the short-circuit ring and the laminated iron core, It has, The rotor is formed of the resin composition described in any one of 1 to 11., wherein the third member is a rotor. [Effects of the Invention]
[0006] According to the present invention, the heat dissipation characteristics of a rotor used in induction electric machines can be improved. [Brief explanation of the drawing]
[0007] [Figure 1] This is a schematic cross-sectional view showing an induction motor according to an embodiment. [Figure 2] This is a schematic side view showing the rotor according to the embodiment. [Figure 3] This is a schematic perspective view showing the rotor according to the embodiment. [Figure 4] FIG. 2 is a perspective view schematically showing a rotor in a state where a resin layer according to the embodiment is removed. [Figure 5] FIG. 4 is a side view schematically showing a cage conductor according to the embodiment. [Mode for Carrying Out the Invention]
[0008] Hereinafter, embodiments of the present invention will be described with reference to the drawings. In all the drawings, the same components are denoted by the same reference numerals, and descriptions thereof are appropriately omitted.
[0009] <Outline of Induction Motor> FIG. 1 is a cross-sectional view schematically showing an induction motor 1 according to the present embodiment. FIG. 2 is a side view schematically showing the rotor 10. FIG. 3 is a perspective view schematically showing the rotor 10. FIG. 4 is a view showing a state in which the resin layer 40 is removed from the rotor 10 of FIG. 3. FIG. 5 is a perspective view of the cage conductor 30. Note that illustration of the cooling flow passage 50 is omitted in FIGS. 2 to 4.
[0010] The induction motor 1 includes a cylindrical stator 5, a rotor 10 surrounded by the stator 5 and rotationally driven, a shaft 3 provided at the center of the rotor 10, and a housing 2 that accommodates these components. The rotor 10 is a so-called cage rotor. The rotation axis AX is the rotation center of the rotor 10. The direction in which the rotation axis AX extends, that is, the left-right direction in FIG. 1, may be referred to as the axial direction.
[0011] The housing 2 has a housing cylindrical portion 2a that accommodates the stator 5, and a housing end portion 2b that closes one axial end (here, the left side in the drawing) of the housing cylindrical portion 2a. A part (an introduction portion 51, a header portion 53, and a discharge portion 54) of a cooling flow passage 50 to be described later is formed in the housing end portion 2b. As the material of the housing 2, for example, an aluminum alloy (cast casting), a resin material, or a combination thereof can be used.
[0012] Bearings 4 are housed in the openings at both ends of the housing cylindrical portion 2a, rotatably supporting the shaft 3. The stator 5 has a stator core fixed to the housing 2 (housing cylindrical portion 2a) and a coil assembled to the stator core.
[0013] A cooling channel 50 through which coolant CL circulates is formed in the shaft 3 and the housing end 2b, and is connected to an external radiator 9. Specifically, the shaft 3 is provided with a cooling recess 52 at one end (the left end in this illustration), which is formed as a hole with a circular cross-section and a concave shape in the axial direction. The cooling recess 52 is provided in the axial direction up to the point where the shaft 3 protrudes from the other end of the laminated iron core 20. The housing end 2b is provided with a tubular inlet 51, a header 53, and a discharge 54. One end of the inlet 51 is connected to the radiator 9, and the other end is inserted into the cooling recess 52. The header 53 is connected to the cooling recess 52 and temporarily stores the coolant CL. The discharge 54 connects the radiator 9 and the header 53. Coolant CL supplied from the radiator 9 is introduced into the cooling recess 52 from the inlet 51, passes through the header 53, and is returned to the radiator 9 from the discharge 54.
[0014] <rotor> The rotor 10 is a squirrel-cage rotor and comprises a laminated iron core 20, a squirrel-cage conductor 30, and a resin layer 40. The laminated iron core 20 has a structure in which multiple electromagnetic steel sheets are laminated in the axial direction, and its outer shape is generally cylindrical. The electromagnetic steel sheets are annular thin sheets. Each of the multiple electromagnetic steel sheets is fixed to each other by crimping, welding, or bonding. A shaft 3 extending in the direction of the laminated electromagnetic steel sheets is attached to the center of the laminated iron core 20. The thickness of a single sheet of electrical steel is, for example, 100 μm or less. The upper limit of the sheet thickness is preferably 75 μm or less, and more preferably 50 μm or less. There is no particular lower limit, but a practical value is 20 μm or more, and more preferably 30 μm or more.
[0015] The squirrel-cage conductor 30 has a plurality of metal rods 33 extending in the lamination direction of the laminated core 20 (more specifically, a plurality of electromagnetic steel sheets), and a pair of short-circuit rings (first short-circuit ring 31 and second short-circuit ring 32) provided at a certain distance from each end of the laminated core 20. The material of the metal rods 33 and the first and second short-circuit rings 31 and 32 is a conductive metallic material, such as copper, aluminum, and their alloys. The first and second short-circuit rings 31 and 32 are, for example, identical in shape.
[0016] Multiple metal rods 33 are arranged outside the circumferential surface 23 (outer circumference) of the laminated iron core 20 at regular intervals in the circumferential direction. The multiple metal rods 33 are electrically connected to the first short-circuit ring 31 and the second short-circuit ring 32, which are located at both ends of the rotating shaft AX in the axial direction. Here, the first to sixth metal rods 33a to 33f are, for example, of the same thickness and are arranged at 60-degree intervals with respect to the rotating shaft AX. Note that the first to sixth metal rods 33a to 33f may be provided parallel to the rotating shaft AX as shown in the figure, or they may extend in a direction twisted with respect to the rotating shaft AX, that is, in a direction that is not parallel but does not intersect. In other words, the lamination direction (the direction in which the metal rods 33 extend) can also be said to be the direction in which the first short-circuit ring 31 and the second short-circuit ring 32 are connected by a straight line, and may be parallel to the rotating shaft AX, or in a direction twisted with respect to the rotating shaft AX.
[0017] <Resin layer> The resin layer 40 is provided as a cured product of the resin composition. The resin composition includes a thermosetting resin (excluding silicone resin) and is used to fill at least a portion of the space between the squirrel-cage conductor 30 and the laminated iron core 20. "Filling at least a portion" means that all of the elements constituting the squirrel-cage conductor 30 (first short-circuit ring 31, second short-circuit ring 32, metal rod 33) and the laminated iron core 20 may be embedded in the resin layer 40, or some may be exposed from the resin layer 40, or there may be cavities within the resin layer 40.
[0018] In this embodiment, as shown in Figures 2 and 3, the metal rods 33 (first to sixth metal rods 33a to 33f) are completely embedded in the resin layer 40. As shown in Figure 2, in the first short-circuit ring 31 and the second short-circuit ring 32, the surface facing the laminated iron core 20 is covered by the resin layer 40, but the surface opposite to the surface corresponding to the laminated iron core 20 is exposed from the resin layer 40. The details are explained below.
[0019] The resin layer 40 is provided between the laminated iron core 20 and the cage-type conductor 30. Specifically, the resin layer 40 has a first end resin layer 41, a second end resin layer 42, and a circumferential resin layer 43. The circumferential resin layer 43 is also called the first member, and the first end resin layer 41 and the second end resin layer 42 are also called the third member. The first end resin layer 41, the second end resin layer 42, and the circumferential resin layer 43 are provided integrally from the same resin composition, but they may be provided as separate components, in which case the resin compositions may be the same or different. In addition, any of the first end resin layer 41, the second end resin layer 42, and the circumferential resin layer 43 may be omitted. For example, the circumferential resin layer 43 may be omitted, and the structure may consist only of the first end resin layer 41 and the second end resin layer 42, or the first end resin layer 41 and the second end resin layer 42 may be omitted, and the structure may consist only of the circumferential resin layer 43. Depending on the required heat dissipation performance, the necessary configuration may be adopted.
[0020] The first end resin layer 41 is provided on the outside of the first end 21 of the laminated core 20. Here, the first end resin layer 41 is provided between the first end 21 of the laminated core 20 and the first short-circuit ring 31. The first end resin layer 41 covers the surface of the first short-circuit ring 31 that faces the first end 21 of the laminated core 20, but does not cover the surface on the opposite side. The first end resin layer 41 may also completely cover the first short-circuit ring 31. With this configuration, heat from the first short-circuit ring 31 and the metal rod 33 can be effectively dissipated. That is, the first end resin layer 41 can transfer heat from the first short-circuit ring 31 and the metal rod 33 to the laminated core 20, and further transfer it to the cooling water CL in the cooling channel 50 of the shaft 3. In addition, heat can be dissipated from the surface of the first end resin layer 41.
[0021] The second end resin layer 42 is provided on the outside of the second end 22 of the laminated core 20. Here, the second end resin layer 42 is provided between the second end 22 of the laminated core 20 and the second short-circuit ring 32. The second end resin layer 42 covers the side of the second short-circuit ring 32 that faces the second end 22 of the laminated core 20, but does not cover the side opposite to that. The second end resin layer 42 may also completely cover the second short-circuit ring 32. With this configuration, heat from the second short-circuit ring 32 and the metal rod 33 can be effectively dissipated. That is, the second end resin layer 42 can transfer heat from the second short-circuit ring 32 and the metal rod 33 to the laminated core 20, and further transfer it to the cooling water CL in the cooling channel 50 of the shaft 3. In addition, heat can be dissipated from the surface of the second end resin layer 42.
[0022] The circumferential resin layer 43 is provided on the outside of the circumferential surface 23 of the laminated core 20. For example, the circumferential resin layer 43 is formed to a constant thickness on the outside of the circumferential surface 23 of the laminated core 20, and extends to the same position as the outer edge of the first short-circuit ring 31 (or second short-circuit ring 32) when viewed from the axial end (for example, from the first short-circuit ring 31 side). The circumferential resin layer 43 completely covers the metal rods 33 (first to sixth metal rods 33a to 33f) on the outside of the circumferential surface 23 of the laminated core 20. However, a part of the metal rods 33 may be exposed from the circumferential resin layer 43. For example, in the case of a metal rod 33, the surface facing the circumferential surface 23 of the laminated core 20 may be covered by the resin layer 40, and the outer surface may be exposed from the resin layer 40. The circumferential resin layer 43 penetrates between the electrical steel sheets that make up the laminated core 20. As a result, at least the area near the circumferential resin layer 43 in the gaps between the electrical steel sheets is filled, improving the variation in temperature distribution between the electrical steel sheets of the laminated core 20, and also improving the variation in temperature distribution of the laminated core 20 as a whole. As a result, the heat dissipation characteristics are improved. Conventionally, heat dissipation characteristics to the extent that the variation in temperature distribution of the laminated core 20 would be a problem were not required. However, in recent years, with the increase in power output of induction motors 1, further improvement in heat dissipation characteristics has been required, and by providing the circumferential resin layer 43, such heat dissipation characteristics can be improved.
[0023] <Materials for the resin layer (resin composition)> The resin layer 40 is a cured product of the resin composition as described above. The resin composition includes a thermosetting resin other than silicone resin, a curing agent, and an inorganic filler. The thermosetting resin preferably comprises one or more materials selected from the group consisting of epoxy resins, phenolic resins, nylon, and urethane. Epoxy resins are particularly preferred from the viewpoint of ensuring fluidity during molding.
[0024] (Epoxy resin) Examples of epoxy resins include bifunctional or crystalline epoxy resins such as biphenyl-type epoxy resins, bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, stilbene-type epoxy resins, and hydroquinone-type epoxy resins; novolac-type epoxy resins such as cresol novolac-type epoxy resins, phenol novolac-type epoxy resins, and naphthol novolac-type epoxy resins; phenol aralkyl-type epoxy resins such as phenylene skeleton-containing phenol aralkyl-type epoxy resins, biphenylene skeleton-containing phenol aralkyl-type epoxy resins, and phenylene skeleton-containing naphthol aralkyl-type epoxy resins; trifunctional epoxy resins such as triphenolmethane-type epoxy resins and alkyl-modified triphenolmethane-type epoxy resins; modified phenol-type epoxy resins such as dicyclopentadiene-modified phenol-type epoxy resins and terpene-modified phenol-type epoxy resins; and heterocyclic epoxy resins such as triazine nucleus-containing epoxy resins. These may be used individually or in combination of two or more types.
[0025] The epoxy resin preferably comprises one or more epoxy resins selected from the group consisting of phenol novolac type epoxy resins and phenol aralkyl type epoxy resins, and more preferably comprises a cresol novolac type epoxy resin, from the viewpoint of ensuring the fluidity of the resulting resin composition and the strength of the cured product of the resin composition.
[0026] The epoxy resin content in the resin composition may be, for example, 3% by mass or more, preferably 8% by mass or more, more preferably 10% by mass or more, and even more preferably 12% by mass or more, based on the total solid content of the resin composition, from the viewpoint of improving the fluidity of the resulting resin composition and improving workability and moldability. Furthermore, from the viewpoint of improving the strength and heat resistance of the cured product formed using the resin composition, the epoxy resin content is preferably 30% by mass or less, and more preferably 20% by mass or less, relative to the total solid content of the resin composition.
[0027] In this embodiment, the total solid content of the resin composition refers to the non-volatile content in the resin composition, which is the remainder after removing volatile components such as water and solvents. Also, in this embodiment, the content relative to the total amount of the resin composition refers to the content relative to the total solid content of the resin composition excluding the solvent, if a solvent is included.
[0028] In one embodiment, the resin composition may further contain thermosetting resins other than the epoxy resin described above. Examples of usable thermosetting resins include bismaleimide resin, benzoxazine resin, phenol resin, urea resin, melamine resin, unsaturated polyester resin, polyurethane resin, diallyl phthalate resin, silicone resin, cyanate resin, polyimide resin, polyamideimide resin, and benzocyclobutene resin. These thermosetting resins may be used individually or in combination of two or more.
[0029] (Hardening agent) The curing agent used in the thermosetting resin composition of this embodiment is not limited as long as it is commonly used in resin compositions containing epoxy resins, but examples include phenolic resin curing agents, amine curing agents, acid anhydride curing agents, mercaptan curing agents, and other curing agents. Among these, phenolic resin curing agents are preferred in terms of the balance of flame resistance, moisture resistance, electrical properties, curability, and storage stability.
[0030] Examples of phenolic resin curing agents include those commonly used in epoxy resin compositions, and more specifically, novolac resins obtained by condensing or co-condensing phenols such as phenols (including phenol novolac resins, cresol novolac resins), cresol, resorcinol, catechol, bisphenol A, bisphenol F, phenylphenol, aminophenol, α-naphthol, β-naphthol, dihydroxynaphthalene, etc.) with formaldehyde or ketones under an acidic catalyst; phenolic aralkyl resins having a phenylene skeleton synthesized from the above-mentioned phenols and dimethoxyp-xylene or bis(methoxymethyl)biphenyl; phenolic aralkyl resins such as phenolic aralkyl resins having a biphenylene skeleton; and phenolic resins having a trisphenylmethane skeleton. These may be used individually or in combination of two or more. The phenolic resin curing agent preferably contains a phenolic novolac resin.
[0031] When the curing agent is a phenolic resin-based curing agent, the equivalent ratio of epoxy resin to curing agent, i.e., the ratio of (moles of epoxy groups in the epoxy resin / moles of phenolic hydroxyl groups in the phenolic resin-based curing agent), is preferably 0.5 or higher, more preferably 0.6 or higher, and even more preferably 0.8 or higher, from the viewpoint of improving the moldability and reliability of the resin composition. Also, from the same viewpoint, the above ratio is preferably 2 or less, more preferably 1.8 or less, and even more preferably 1.5 or less.
[0032] Examples of amine-based curing agents include aliphatic polyamines such as diethylenetriamine (DETA), triethylenetetramine (TETA), and metaxylylenediamine (MXDA); aromatic polyamines such as diaminodiphenylmethane (DDM), m-phenylenediamine (MPDA), and diaminodiphenylsulfone (DDS); and polyamine compounds such as dicyandiamide (DICY) and organic acid dihydrarazines. These may be used individually or in combination of two or more.
[0033] Examples of acid anhydride-based curing agents include alicyclic acid anhydrides such as hexahydrophthalic anhydride (HHPA), methyltetrahydrophthalic anhydride (MTHPA), and maleic anhydride; and aromatic acid anhydrides such as trimellitic anhydride (TMA), pyromellitic anhydride (PMDA), benzophenonetetracarboxylic acid (BTDA), and phthalic anhydride. These may be used individually or in combination of two or more.
[0034] Examples of mercaptan-based curing agents include trimethylolpropanetris (3-mercaptobutyrate) and trimethylolethanetris (3-mercaptobutyrate). These may be used individually or in combination of two or more.
[0035] Other curing agents include, for example, isocyanate compounds such as isocyanate prepolymers and blocked isocyanates; and organic acids such as carboxylic acid-containing polyester resins. Note that two or more curing agents from different systems among those listed above may be used in combination.
[0036] The curing agent content in the resin composition is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 3% by mass or more, relative to the total amount of the resin composition, from the viewpoint of achieving excellent fluidity and improving filling and moldability in the resin layer 40 formation process. On the other hand, from the viewpoint of improving the moisture resistance reliability and heat resistance of the cured resin product, the curing agent content is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the total amount of the resin composition.
[0037] (Inorganic fillers) As inorganic fillers, thermally conductive fillers with good thermal conductivity are preferred, such as metal oxides, nitrides, carbides, metal powders, calcium fluoride, carbon, carbon nanotubes, graphite, and carbon fibers. Among these, fused silica such as molten crushed silica and molten spherical silica, silica such as crystalline silica, alumina, aluminum hydroxide, silicon nitride, aluminum nitride, and boron nitride are particularly preferred. These may be used individually or in combination of two or more. From the viewpoint of providing favorable mechanical or thermal properties for the cured resin composition, the inorganic filler preferably contains silica, and more preferably contains one or more selected from the group consisting of crushed silica and molten spherical silica.
[0038] (Average particle size D50 of inorganic filler) The average particle size D50 (median diameter), which is the 50% value of the cumulative distribution function of the particle size distribution of the inorganic filler contained in the thermosetting resin, is between 1 μm and 10 μm. The particle size of the inorganic filler is measured using a laser diffraction particle size distribution analyzer. By setting the average particle size D50 within this range, the fluidity of the resin composition is improved, and filling during molding and penetration into gaps between electrical steel sheets can be facilitated. Because the filler has high thermal conductivity, the heat transfer efficiency between the resin layer 40 and the laminated iron core 20 is improved. In particular, very high heat transfer efficiency can be achieved by using a heat-conductive filler. From the viewpoint of improving the fluidity of the resin composition and enhancing moldability, the particle size is preferably 1.5 μm or larger, and more preferably 2 μm or larger. Furthermore, from the viewpoint of improving filling performance, suppressing the occurrence of unfilled areas, and facilitating penetration into the gaps between the electrical steel sheets of the laminated iron core 20, the average particle size D50 of the inorganic filler is preferably 9 μm or smaller, and more preferably 8 μm or smaller.
[0039] Furthermore, two or more inorganic fillers with different average particle sizes D50 may be used in combination. This makes it possible to more effectively improve the packing performance of the inorganic fillers relative to the total solid content of the resin composition.
[0040] Furthermore, the (D50 / D90) value, calculated from the value of the particle diameter D90 of the inorganic filler at which the cumulative frequency measured using a laser diffraction particle size distribution analyzer reaches 90%, and the value of the average particle size D50 of the inorganic filler, is preferably 0.2 or higher, more preferably 0.25 or higher, and even more preferably 0.3 or higher, from the viewpoint of improving the fluidity of the resin composition. Also, from the viewpoint of improving the ability to fill narrow spaces, the above ratio (D50 / D90) is preferably 1.0 or lower, more preferably 0.9 or lower, and even more preferably 0.8 or lower.
[0041] Here, the particle size of the inorganic filler, specifically D50 and D90, can be obtained by measuring the particle size distribution on a volume basis using a commercially available laser diffraction particle size distribution analyzer (for example, Shimadzu Corporation's SALD-7000).
[0042] (Filler content ratio) The inorganic filler content in the resin composition is 70% to 95% by mass relative to the total mass of the thermosetting resin. From the viewpoint of suppressing the hygroscopicity and thermal expansion of the resin composition and more effectively improving the temperature cycle resistance and moisture resistance of the cured resin composition, the inorganic filler content is preferably 75% or more by mass, and more preferably 80% or more by mass, relative to the total amount of the resin composition. Furthermore, from the viewpoint of more effectively improving the fluidity and filling properties of the resin composition during molding, the inorganic filler content is preferably 90% or less by mass, and more preferably 85% or less by mass, relative to the total amount of the resin composition.
[0043] (Other ingredients) In this embodiment, the resin composition may further contain components other than those described above. For example, the resin composition may further contain a curing accelerator, a coupling agent, a flame retardant, an ion scavenger, a colorant, and an antioxidant.
[0044] (Curing accelerator) The curing accelerator can be any agent that promotes the crosslinking reaction between the epoxy resin and the curing agent, and one commonly used in epoxy resin compositions can be used. Specific examples of curing accelerators include, for example, diazabicycloalkenes and their derivatives such as 1,8-diazabicyclo(5,4,0)undecene-7; organophosphines such as triphenylphosphine and methyldiphenylphosphine; imidazole compounds such as 2-methylimidazole (imidazole-based curing accelerators); and tetra-substituted phosphonium or tetra-substituted borates such as tetraphenylphosphonium-tetraphenylborate.
[0045] Examples of imidazole-based curing accelerators include imidazole, 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-phenylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, and 1-cyanoethyl-2-phenyl Examples include imidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4-methylimidazolyl(1')]-ethyl-s-triazine, isocyanuric acid adducts of 2,4-diamino-6-[2'-methylimidazolyl(1')]-ethyl-s-triazine, isocyanuric acid adducts of 2-phenylimidazole, isocyanuric acid adducts of 2-methylimidazole, 2-phenyl-4,5-dihydroxydimethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole.
[0046] (Coupling agent) As coupling agents, known coupling agents such as various silane compounds including epoxysilane, mercaptosilane, aminosilane, alkylsilane, ureidosilane, vinylsilane, and methacrylicsilane, as well as titanium compounds, aluminum chelates, and aluminum / zirconium compounds can be used. Examples of these include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, vinyltriacetoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-anilinopropyltrimethoxysilane, γ-anilinopropylmethyldimethoxysilane, γ-[bis(β-hydroxyethyl)]aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyl Trimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, phenylaminopropyltrimethoxysilane, γ-(β-aminoethyl)aminopropyldimethoxymethylsilane, N-(trimethoxysilylpropyl)ethylenediamine, N-(dimethoxymethylsilylisopropyl)ethylenediamine, methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, hexamethyldisilane, vinyltrimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, 3-isocyanatetopropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-triethoxysilyl-N-(1,Silane coupling agents such as hydrolysates of 3-dimethylbutylidene)propylamine, isopropyltriisostearoyl titanate, isopropyltris(dioctyl pyrophosphate) titanate, isopropyltri(N-aminoethyl-aminoethyl) titanate, tetraoctylbis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl) phosphite titanate, bis(dioctyl pyrophosphate) oxyacetate titanate Examples of titanate coupling agents include titanate, bis(dioctyl pyrophosphate)ethylene titanate, isopropyl trioctanoyl titanate, isopropyl dimethacrylate isostearoyl titanate, isopropyl toridodecylbenzenesulfonyl titanate, isopropyl isostearoyl diacrylic titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumylphenyl titanate, and tetraisopropyl bis(dioctyl phosphite) titanate. These may be used individually or in combination of two or more. Among these, silane compounds such as epoxysilane, mercaptosilane, aminosilane, alkylsilane, ureidosilane, or vinylsilane are more preferred. Furthermore, from the viewpoint of more effectively improving filling and moldability, the use of secondary aminosilanes, such as phenylaminopropyltrimethoxysilane, is even more preferred.
[0047] When a coupling agent is used, its content is preferably 0.05% by mass or more, more preferably 0.10% by mass or more, relative to the total solid content of the resin composition, from the viewpoint of ensuring favorable fluidity of the resin composition. Furthermore, from the viewpoint of improving the mechanical strength of the cured resin composition, the content of the coupling agent is preferably 1.5% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less, relative to the total solid content of the resin composition.
[0048] (Coloring agent) Examples of colorants include carbon black, red iron oxide, and titanium dioxide. Among these, carbon black is preferred as the colorant. From the viewpoint of obtaining a desirable appearance for the cured resin composition, the colorant content is preferably 0.05% by mass or more, more preferably 0.10% by mass or more, relative to the total amount of the resin composition. Furthermore, from the viewpoint of obtaining a desirable resin viscosity, the colorant content is preferably 1.5% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less, relative to the total amount of the resin composition.
[0049] (Antioxidant) Examples of antioxidants include hindered phenol compounds, hindered amine compounds, and thioether compounds.
[0050] (Thermal conductivity of thermosetting resin compositions) The resin composition of this embodiment has a cured product with a thermal conductivity of, for example, 0.5 W / m·K or higher. The lower limit is preferably 0.8 W / m·K or higher, and more preferably 2 W / m·K or higher. The upper limit is not particularly limited, but as a practical value, it is 20 W / m·K or lower, preferably 15 μm or lower, and more preferably 10 μm or lower. By adjusting the type and content of fillers in the resin composition, a desired thermal conductivity can be obtained. With such thermal conductivity, the heat generated in the squirrel-cage conductor 30 can be effectively transferred to the laminated iron core 20 or dissipated from the surface of the resin layer 40. The method for measuring thermal conductivity is as follows: A resin composition is injected using a transfer molding machine at a mold temperature of 175°C, an injection pressure of 9.8 MPa, and a curing time of 3 minutes to obtain a cured sample of 10 mm × 10 mm × 1 mm. The thermal conductivity of the cured sample is calculated using the following formula from the thermal diffusivity (α) measured by the laser flash method (half-time method), the specific heat (Cp) measured by the DSC method, and the density (ρ) measured in accordance with JIS K 6911. The unit of thermal conductivity is W / m·K. Thermal conductivity [W / m K]=α[mm2 / s] × Cp[J / kg·K] × ρ[g / cm 3 ]
[0051] (Glass transition temperature of thermosetting resin composition) The glass transition temperature (Tg) of the resin composition of the resin layer 40 is 145°C or higher. The lower limit of the glass transition temperature Tg is preferably 175°C or higher, and more preferably 200°C or higher. There is no particular upper limit for the glass transition temperature Tg, but a practical value is 300°C or lower, preferably 275°C or lower, and more preferably 250°C or lower. By setting the glass transition temperature Tg within the above range, the induction motor 1 can be used at high temperatures, and the squirrel-cage conductor 30 becomes more resistant to heat generation, allowing it to be used at high power.
[0052] [Method for producing thermosetting resin compositions] The resin composition of this embodiment can be produced by uniformly mixing the above components and any additives used as needed in a mixer or blender such as a tumbler mixer or Henschel mixer to a predetermined content, and then kneading while heating in a kneader, roll mixer, disper mixer, adi-homogenizer mixer, or planetary mixer. The temperature during kneading must be within a temperature range in which no curing reaction occurs, and although it depends on the composition of the epoxy resin and curing agent, it is preferable to melt-knead at around 70 to 150°C. After kneading, the mixture may be cooled and solidified, and the kneaded material may be processed into powder, granules, tablets, or sheets.
[0053] One method for obtaining a granular resin composition is to pulverize a mixture using a pulverizing device. Alternatively, the mixture may be formed into a sheet and then pulverized. Examples of pulverizing devices include hammer mills, stone mills, and roll crushers.
[0054] As a method for obtaining a granular or powdered resin composition, one can use a granulation method, such as the hot-cut method, in which a small-diameter die is installed at the outlet of a kneading device, and the molten kneaded material discharged from the die is cut to a predetermined length with a cutter or the like. In this case, it is preferable to degas the resin composition before its temperature drops too much after obtaining the granular or powdered resin composition by a granulation method such as the hot-cut method.
[0055] <Manufacturing method for rotors> The manufacturing method for the rotor 10 of this embodiment will be described. First, a squirrel-cage conductor 30 and a laminated iron core 20 are prepared by stacking multiple electromagnetic steel sheets in the axial direction and fixing them in close contact (conductor and laminated iron core preparation process). A cage-shaped conductor 30 and a laminated iron core 20 are placed in a molding die, and a resin layer 40 is formed by insert molding (resin layer formation step). Transfer molding or injection molding can be used as the molding method for the resin composition. In Patent Document 1, which was exemplified in the background art, the resin layer was formed by applying a liquid resin composition from the viewpoint of improving productivity. In other words, the viewpoint of improving the heat transfer characteristics of the laminated iron core 20 by allowing the resin composition to penetrate between the electrical steel sheets was not considered. In this embodiment, the rotor 10 can be manufactured with high precision by employing insert molding using transfer molding or injection molding. Furthermore, compared to coating, the amount of resin composition penetrating between the electrical steel sheets is increased, resulting in improved heat transfer characteristics of the laminated core 20. Through the above process, the rotor 10 shown in Figure 2 is obtained.
[0056] The embodiments of the present invention have been described above, but these are merely examples, and various other configurations can be adopted. Examples of modifications of the rotor 10 are provided below.
[0057] (Variation 1) In the above-described embodiment, an example was given in which, as a conductor provided between the first short-circuit ring 31 and the second short-circuit ring 32, a plurality of metal rods 33 are provided on the outside of the circumferential surface 23 of the laminated iron core 20. In Modification 1, the rotor 10 has a plurality of through holes provided in the lamination direction of the laminated core 20. The squirrel-cage conductor 30 has a first short-circuit ring 31, a second short-circuit ring 32, and a plurality of conductors (metal rods 33). The plurality of metal rods 33 extend inside the through holes, and both ends protrude from the laminated core 20. With the metal rods 33 arranged in the through holes of the laminated core 20, a resin layer 40 is provided using the resin composition described above.
[0058] Multiple metal rods 33 may be made from pre-prepared rod materials, or they may be formed by casting a metal material such as aluminum into the through-hole. In either case, a gap will be created between the inner wall surface of the through-hole and the metal rod 33. When a metal material is cast, the gap will be created due to the difference in the coefficient of thermal expansion between the laminated iron core 20 and the metal rod 33. The resin composition is used to fill at least a portion of the gap between the through-hole and the metal rod 33. At least a portion is, for example, 50% or more of the gap, preferably 70% or more, and more preferably 90% or more. In other words, the resin layer 40 is provided in the gap between the through-hole and the metal rod 33. The resin layer 40 provided in the gap between the through-hole and the metal rod 33 is also called the second member. The resin layer 40 may be provided only on the second member, or, in addition to the second member, it may have a first member (circumferential resin layer 43) and a third member (first end resin layer 41, second end resin layer 42), as in the embodiment, or it may be provided only on a part of them.
[0059] (Modification 2) In modified example 2, the rotor 10 has a plurality of through holes provided in the lamination direction of the laminated core 20. The squirrel-cage conductor 30 has a first short-circuit ring 31, a second short-circuit ring 32, and a plurality of conductors (metal rods 33). The plurality of metal rods 33 extend inside the through holes. With the metal rods 33 positioned in the through holes of the laminated core 20, a resin layer 40 is provided using the resin composition described above. Specifically, the resin layer 40 has at least one of a first end resin layer 41 and a second end resin layer 42 (second member). In other words, the resin composition is used to fill at least a portion of the space between the first short-circuit ring 31 and the second short-circuit ring 32 and the laminated core 20. "At least a part" means, for example, when a thin surface layer is formed between the first short-circuit ring 31 and the first end 21 of the laminated core 20 and / or between the second short-circuit ring 32 and the second end 22, or when it is provided in a region between the first short-circuit ring 31 and the second short-circuit ring 32 and the laminated core 20 with a certain volume.
[0060] <Summary of the features of this embodiment> The features of this embodiment can be briefly summarized as follows: 1. A resin composition for use in a rotor 10 having a laminated core 20 made of multiple laminated electromagnetic steel sheets and a conductor (metal rod 33) extending in the lamination direction of the laminated core 20, the resin composition comprising a thermosetting resin (excluding silicone resin). 2. The resin composition according to 1, wherein the thermosetting resin comprises one or more materials selected from the group consisting of epoxy resin, phenolic resin, nylon, and urethane. 3. The resin composition according to 1. or 2., wherein the glass transition temperature Tg of the thermosetting resin is 145°C or higher. 4. The resin composition according to 1. or 2., wherein the filler content in the thermosetting resin is 70% by mass or more and 95% by mass or less, based on the total mass of the thermosetting resin. 5. The resin composition according to 1. or 2., wherein the average particle size D50 in the particle size distribution of the filler contained in the thermosetting resin is 1 μm or more and 10 μm or less. 6. The resin composition according to 1. or 2., wherein the thermosetting resin is solid. 7. The resin composition according to 1. or 2., wherein the thermal conductivity of the thermosetting resin is 0.5 W / m·K or higher. 8. The resin composition according to 1. or 2., wherein the thermosetting resin comprises a thermal conductive filler. 9. The conductor (metal rod 33) is positioned outside the side surface (circumferential surface 23) of the laminated iron core 20. The resin composition according to 1. or 2., which is used to fill at least a portion of the space between the conductor (metal rod 33) and the laminated iron core 20. 10. The rotor 10 has through holes provided in the stacking direction of the laminated iron core 20, The conductor (metal rod 33) extends inside the through hole, The resin composition according to 1. or 2., which is used to fill at least a portion of the gap between the through hole and the conductor (metal rod 33). 11. The rotor 10 has through holes provided in the stacking direction of the laminated iron core 20, and short-circuiting portions (first short-circuiting ring 31, second short-circuiting ring 32) that short-circuit the plurality of metal rods 33 protruding from the through holes, The resin composition according to 1. or 2., which is used to fill at least a portion of the space between the short-circuit portion (first short-circuit ring 31, second short-circuit ring 32) and the laminated iron core 20. 12. A laminated iron core 20 made by stacking multiple steel plates, Multiple conductors (metal rods 33) are arranged outside the side surface (circumferential surface 23) of the laminated iron core 20, A first member (circumferential resin layer 43 and,) is provided in at least a portion between the conductor and the laminated iron core 20. It has, The rotor 10 is formed of the resin composition described in 9. as the first member (circumferential resin layer 43). 13. A laminated iron core 20 made by stacking multiple steel plates, The through holes provided in the stacking direction of the laminated iron core 20, A conductor (metal rod 33) is placed in the through hole, A second member formed in the gap between the through hole and the conductor (metal rod 33), It has, The rotor 10 is formed of the resin composition described in 1. or 2., the second member. 14. A laminated iron core 20 made by stacking multiple steel plates, The laminated iron core 20 has through holes that penetrate from one end to the other in the lamination direction, A conductor (metal rod 33) is placed in the through hole, A short-circuit ring (first short-circuit ring 31, second short-circuit ring 32) is formed by short-circuiting the multiple conductors protruding from the through-hole, A third member (first end resin layer 41, second end resin layer 42) is formed in the space between the short-circuit ring (first short-circuit ring 31, second short-circuit ring 32) and the laminated iron core 20, It has, The rotor 10 is formed by the resin composition described in 1. or 2., wherein the third member (first end resin layer 41, second end resin layer 42) is formed by the resin composition described in 1. or 2. [Examples]
[0061] The present invention will be described in detail below using examples, but the present invention is not limited in any way to the descriptions of these examples.
[0062] The raw material components used in each example and comparative example are shown below. (Epoxy resin) • Epoxy resin 1: Orthocresol novolac type epoxy resin (manufactured by DIC Corporation, product name "EPICRON N-670") • Epoxy resin 2: Orthocresol novolac type epoxy resin (manufactured by DIC Corporation, product name "EPICRON N-660") • Epoxy resin 3: Biphenyl-type epoxy resin (manufactured by Mitsubishi Chemical Corporation, YX-4000K)
[0063] (Hardening agent) • Hardener 1: Novolac-type phenolic compound (manufactured by Sumitomo Bakelite Co., Ltd., PR-51470) • Hardener 2: Novolac-type phenolic compound (manufactured by Sumitomo Bakelite Co., Ltd., PR-51714) • Hardener 3: Triphenolmethane-type phenolic resin (manufactured by Meiwa Chemicals Co., Ltd., MEH-7500)
[0064] (Inorganic filler) • Inorganic filler 1: Molten spherical silica (manufactured by Denka Co., Ltd., FB-950) • Inorganic filler 2: Molten spherical silica (manufactured by Denka Co., Ltd., FB-105) • Inorganic filler 3: Molten crushed silica (manufactured by Fumitec Co., Ltd., FMT-15C) • Inorganic filler 4: Glass fiber (manufactured by Nitto Boseki Co., Ltd., CS3E479) • Inorganic filler 5: Crystallized silica (manufactured by Ryusen Co., Ltd., HFC-7) • Inorganic filler 6: Molten spherical alumina (manufactured by Denka Co., Ltd., DAB-45SI)
[0065] (Curing accelerator) • Curing accelerator 1: Tetraphenylphosphonium 2,3-dihydroxynaphthalate • Curing accelerator 2: 2-phenyl-4,5-dihydroxymethylimidazole (manufactured by Shikoku Chemicals Co., Ltd., 2PHZ-PW)
[0066] (Release agent) • Wax 1: Carnauba wax (manufactured by Toa Chemical Co., Ltd., TOWAX-132)
[0067] (Silane coupling agent) • Silane coupling agent 1: N-phenyl-3-aminopropyltrimethoxysilane (manufactured by Toray Dow Corning Co., Ltd., CF-4083) (Coloring agent) • Coloring agent 1: Carbon black (manufactured by Mitsubishi Chemical Corporation, Carbon #5)
[0068] (Preparation of resin composition) First, the raw materials formulated according to Table 1 were mixed at room temperature using a mixer, and then roll-kneaded at a temperature between 70°C and 110°C. Next, the resulting mixture was cooled and then pulverized to obtain the resin composition.
[0069] The following measurements were performed on the resin compositions obtained in each example. The measurement results are shown in Table 1.
[0070] (Glass transition temperature) For each example, the glass transition temperature of the cured resin composition was measured as follows. First, the resin composition was injected using a transfer molding machine at a mold temperature of 175°C, an injection pressure of 9.8 MPa, and a curing time of 3 minutes to obtain a 15 mm × 4 mm × 4 mm test specimen. Next, the obtained test specimen was post-cured at 175°C for 4 hours, and then measured using a thermomechanical analyzer (TMA100, manufactured by Seiko Electronics Industries, Ltd.) under conditions of a measurement temperature range of 40°C to 300°C and a heating rate of 5°C / min. The glass transition temperature was calculated from these measurement results.
[0071] (Thermal conductivity) The resin compositions obtained in each example were injected and molded using a transfer molding machine at a mold temperature of 175°C, an injection pressure of 9.8 MPa, and a curing time of 3 minutes to obtain cured bodies measuring 10 mm × 10 mm × 1 mm. The thermal conductivity of the obtained cured material was calculated using the following formula, based on the thermal diffusivity (α) measured by the laser flash method (half-time method), the specific heat (Cp) measured by the DSC method, and the density (ρ) measured in accordance with JIS K 6911. The unit of thermal conductivity is W / m·K. Thermal conductivity [W / m K]=α[mm 2 / s] × Cp[J / kg·K] × ρ[g / cm 3 ]
[0072] [Table 1] [Explanation of symbols]
[0073] 1. Induction motor 2 Housing 3 shafts 4 bearings 5 status 10 rotors 20 Laminated Iron Core 30 Cage-shaped conductors 31 First Short-Circuit Ring 32 Second Short-Circuit Ring 33 Metal rod 40 resin layer 41. First end resin layer (third member) 42 Second end resin layer (third member) 43. Peripheral resin layer (first component) 50 Cooling channel
Claims
1. A resin composition used in a rotor having a laminated core made of multiple laminated electromagnetic steel sheets and a conductor extending in the lamination direction of the laminated core, A resin composition containing a thermosetting resin (excluding silicone resin).
2. The resin composition according to claim 1, wherein the thermosetting resin comprises one or more materials selected from the group consisting of epoxy resin, phenolic resin, nylon, and urethane.
3. The resin composition according to claim 1 or 2, wherein the glass transition temperature of the thermosetting resin is 145°C or higher.
4. The resin composition according to claim 1 or 2, wherein the filler content in the thermosetting resin is 70% by mass or more and 95% by mass or less based on the total mass of the thermosetting resin.
5. The resin composition according to claim 1 or 2, wherein the average particle size D50 in the particle size distribution of the filler contained in the thermosetting resin is 1 μm or more and 10 μm or less.
6. The resin composition according to claim 1 or 2, wherein the thermosetting resin is solid.
7. The resin composition according to claim 1 or 2, wherein the thermal conductivity of the thermosetting resin is 0.5 W / m·K or higher.
8. The resin composition according to claim 1 or 2, wherein the thermosetting resin comprises a thermal conductive filler.
9. The conductor is positioned outside the side surface of the laminated iron core, The resin composition according to claim 1 or 2, which is used to fill at least a portion of the space between the conductor and the laminated iron core.
10. The rotor has through holes provided in the stacking direction of the stacked iron core, The conductor extends inside the through hole, The resin composition according to claim 1 or 2, wherein the resin composition is used to fill at least a portion of the gap between the through hole and the conductor.
11. The rotor has through holes provided in the stacking direction of the laminated iron core, and short-circuit portions that short-circuit a plurality of conductors protruding from the through holes, The resin composition according to claim 1 or 2, which is used to fill at least a portion of the space between the short-circuit portion and the laminated iron core.
12. A laminated iron core made by stacking multiple steel plates, Multiple conductors arranged on the side surface of the laminated iron core, A first member provided in at least a portion between the conductor and the laminated iron core, It has, The first member is a rotor formed from the resin composition described in claim 9.
13. A laminated iron core made by stacking multiple steel plates, The through holes provided in the stacking direction of the laminated iron core, A conductor arranged in the through hole, A second member formed in the gap between the through hole and the conductor, It has, The rotor is formed of the resin composition described in claim 10.
14. A laminated iron core made by stacking multiple steel plates, The laminated core has a through hole that penetrates from one end to the other in the lamination direction, A conductor arranged in the through hole, A short-circuit ring formed by short-circuiting multiple conductors protruding from the through-hole, A third member formed in the space between the short-circuit ring and the laminated iron core, It has, The rotor is formed of the resin composition described in claim 1 or 2.
Citation Information
Patent Citations
JP6877657A